The Role of Work Motivation, Work Discipline, and Work Ethic in Improving Employee Performance - Nadya Sriagustin Hosen; Mokhamad Natsir; Boge Triatmanto (Innovation Business Management and Accounting Journal, 2024)
The aim of this research is to describe motivation, discipline, work ethic and employee performance and analyze the level of significance of the influence of motivation, discipline and work ethic simultaneously, partially and dominantly on the performance of PT. Kerry Express Indonesia. This research is causal comparative and explanatory. The investigation was conducted at PT. Kerry Express Indonesia. This research includes all 60 employees at PT. Kerry Express Indonesia as the population and sample. Due to the manageable size of the population, a census research approach was employed, involving all employees as respondents. The analysis conducted includes descriptive analysis and multiple linear regression analysis, which will be subsequently assessed for hypotheses. The study findings indicate that motivation, work discipline, and work ethic have a notable impact on the performance of employees at PT Kerry Express Indonesia. Employee performance is positively influenced by motivation, work discipline, and work ethic, which result in timely completion of tasks in response to instructions. The most influential factor on employee effectiveness is their work ethic. This research can be utilized as input for PT. Kerry Express Indonesia to assess employees' attitudes towards work motivation, work discipline, and work ethic, as a strategic measure to enhance the company's performance.